Ophthalmic immune-related adverse events associated with immune checkpoint inhibitors - Gan, Linyang; Chen, Huan; Liu, Xiaowei; Zhang, Li (Frontiers in Immunology, 2023)
Purpose To investigate the incidence of immune-related adverse events (irAEs) of immune checkpoint inhibitor (ICI) therapy and to report the clinical features, management, and outcomes of ophthalmic irAEs. Methods We retrospectively reviewed the medical records of patients who received ICI therapy from January 2016 to September 2022 at Peking Union Medical College Hospital and analyzed the incidence of systemic and ophthalmic adverse effects of this therapy. Results Of 962 patients, 248 (25.8%) experienced irAEs. The first-year incidences of total irAEs and ophthalmic irAEs were 23.5% and 1.1%. The most common ICI received by the patients was pembrolizumab (373; 38.8%). Nearly half of the patients (477; 49.6%) had lung cancer. Combination therapy was associated with an increased incidence of irAEs without statistical significance. Patients with lung cancer presented with an increased incidence of total irAEs (p = 0.003) and ophthalmic irAEs (p = 0.032). Eleven patients had ophthalmic manifestations, including ophthalmoplegia (6/11), conjunctivitis (3/11), reactive cutaneous capillary endothelial proliferation (RCCEP) (1/11), and orbital inflammation (1/11). Eight patients had concomitant extra-ophthalmic irAEs. Furthermore, ICIs were discontinued in nine patients, and most ophthalmic manifestations were well controlled with topical and systemic steroids. Ten patients were treated with intravenous or oral steroids. However, cancer progression occurred in five out of eleven patients after the interruption of ICIs. Conclusion IrAEs are correlated with ICI regimens and underlying neoplasia. In our Chinese cohort, patients have a higher risk of ophthalmoplegia than uveitis. Early recognition and multidisciplinary consultation are crucial for optimal treatment of ophthalmic irAEs.